Assessing Nepal’s military diplomacy: Neighborhood and beyond - Bhattarai, Gaurav (Unity Journal, 2020)
People often speculate that small countries hardly ever exercise military diplomacy since the latter presume that hard power instruments, including security forces and coercion are the apparatus of powerful countries. Because of its geopolitical location between two bigger countries, Nepal has been successfully exercising military diplomacy in the course of history. Owing to the same fact, this paper aims at assessing Nepal’s military diplomacy towards its immediate neighbors—India and China, and even beyond its neighborhood. In this paper, beyond neighborhood refers to the Nepali Army’s role in United Nations peacekeeping missions in different conflictafflicted countries. Thus, the article concludes with a note that Nepali Army as an established institution of the country has reposed its exceptional capability of exercising the modern-day diplomacy at both levels—neighborhood and beyond.